Consistency of Compressive Strength in Concrete with 10% Rice Husk Ash Substitution - Alfaridh Pasya, Salman; Bima Mahardana, Zendy; Mustofa, Imam; Iwan Candra, Agata (UKaRsT, 2025)
Using rice husk ash (RHA) in concrete technology represents a significant innovation in promoting sustainability. The pozzolanic properties of RHA enhance concrete quality through microstructural refinement while mitigating environmental impacts. However, replacing 10% of cement with RHA has inconsistent effects on compressive strength. Such variability may limit the broader application of RHA in structural concrete due to uncertainties in performance prediction, quality assurance, and design safety. While some studies report strength improvements, others note reductions often attributed to limited samples size, material inconsistencies, and variations in mixing or curing processes. This study aims to statistically validate the consistency of compressive strength in concrete with 10% RHA substitution by increasing the sample size and controlling key variables. Nine specimens per test condition were evaluated using a water-cement ratio of 0.53, submersion curing and ASTM C39 testing standards. Compressive strength assessment was conducted at 7 days. The result show a 7.54% increase in compressive strength, from 22.71 MPa to 24.42 MPa, with a coefficient of variation (CV) of 2.26%, well below the 10% threshold. In contrast, earlier studies with smaller sample sizes reported CVs as high as 42.65%, indicating greater statistical variability. This improvement is attributed to the increased sample size, material quality control, and uniform mixing, which ensured homogeneous RHA distribution and optimized pozzolanic reactions. By applying a controlled-variable approach and increasing the sample size, this study addresses prior inconsistencies and reinforces the validity of RHA as a viable cement substitute in concrete.